ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DI KECAMATAN CANDIPURO KABUPATEN LUMAJANG - Vilmia Farida; Ahmad Waluya Jati; Riska Harventy (Universitas Muhammadiyah Malang, 2018)
The purpose of this research is to analyze the accountability of Village Fund Allocation management in Candipuro District, Lumajang Regency which consists of planning, implementation, reporting and accountability. This research was conducted in ten villages in the Candipuro District. Data collection techniques were carried out by using documentation and interview techniques. The analysis technique used is descriptive analysis with a qualitative approach.The results of this study indicate that in the District of Candipuro at the planning, implementation and reporting stages have implemented the principles of accountability and the principle of transparency. whereas at the accountability stage it is good enough even though there is one village that is physically not yet accountable because the construction has not yet been completed.